The Impact of Price and Service Quality on Patient Loyalty at Pratama BHG Dental Polyclinic with Patient Satisfaction as an Intervening Variable - Restu Aritonang; Bernard T. Widjaja; Wani Devita Gunardi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to identify and analyze the influence of 1) price on patient loyalty, 2) service quality on patient loyalty, 3) patient satisfaction on patient loyalty, 4) price on patient satisfaction, 5) service quality on patient satisfaction, 6) price on patient loyalty through patient satisfaction, 7) service quality on patient loyalty through patient satisfaction. The data used is primary data obtained from the responses of 100 respondents. The data analysis tool used is path analysis. The instrument testing results concluded that all variables are valid and reliable as data collection tools. The data analysis results found that: 1) price has a positive effect on patient loyalty, 2) service quality has a positive effect on patient loyalty, 3) patient satisfaction has a positive effect on patient loyalty, 4) price has a positive effect on patient satisfaction, 5) service quality has a positive effect on patient satisfaction, 6) price has a positive effect on patient loyalty through patient satisfaction, 7) service quality has a positive effect on patient loyalty through patient satisfaction.